A “cidade dos lagos”: narrativas ancestrais sobre as estearias no município de Penalva – MA - MARTINS, Dayse Marinho (2024)
Study on the stye sites located in the municipality of Penalva – MA. Stearias are archaeological sites formed by the concentration of tree trunks of trees placed on the beds of rivers and lakes in Baixada Maranhense between the beginning of the Christian era and the year 1200 A.D. The elaboration of ancestral narratives by the population about the formation of these pre-colonial settlements is analyzed, characterizing them, discussing the processes interpretative elaboration during the constitution of the municipality of Penalva-MA. To this end, the theoretical approach of Cultural History considering culture according to Chartier is taken as a basis, focusing on practices and representations. The perspective of Global History is approached, highlighting connections and beyond the borders of the nation-state framework. The concepts of memory, narrative, identity and territory are also articulated. The research is qualitative, encompassing procedural methods, bibliographical and documentary research and Oral History in thematic modality based on field research with focus group observation and recording, through semi-structured interviews and Google forms, the perceptions of the city's residents. of Penalva as an intentional field of study. The analysis is based on the comparative method by articulating reports with written sources, such as Maranhão newspapers from the 20th century located in the digital Hemeroteca of the National Library and Public Library Benedito Leite, publications on the history of Penalva and the archeology of the sites, in addition to works literature, historiography from Maranhão and amateur historians from Penalva-MA. The research is located in the 21st century, and as an approach to the present time, it contemplates the population's interpretation of the stearias, evoking events from the 20th century, in which we can see the elaboration of interpretations about archaeological sites by the population of Penalva. The study highlights the set of ancestral stories that characterize the explanation of the people who live close to the stearias, raising reflections on representations and traditions forged in narratives, as well as actions that make it possible to strengthen the ties between the penal population and the stearias. Therefore, it contributes to enriching the current historiography of Maranhão as it highlights local epistemologies, in addition to promoting the education of historical sense from a community perspective to value cultural heritage.